AN INVESTIGATION INTO THE ROLE OF CORPORATE GOVERNANCE IN STRATEGY IMPLEMENTATION IN KENYAN CORPORATIONS: A CASE STUDY OF INDUSTRIAL AND COMMERCIAL DEVELOPMENT CORPORATION (I.C.D.C.) - WAMBUGU, WILSON (Kabarak University, 2016)
ABSTRACT CORPORATE GOVERNANCE – is the relationship among the board of directors, top management, and the shareholders in determining the direction and performance of the corporation. A case study of INDUSTRIAL AND COMMERCIAL DEVELOPMENT CORPORATION (ICDC) STATING THE PROBLEM – the board of directors exists to protect the interests of the stockholders, so employees may not be represented on the board. METHODOLOGY – a typical corporation structure consists of three main groups, directors, corporate officers, and shareholders, who are identified in the articles of incorporation. KEYFINDINGS – when a corporate is first formed, its original owners are usually its first shareholders. CONCLUSION – a strategy which contradicts an entrenched culture may find itself being quietly, sabotaged by the corporation’s most royal and competent employees. RECOMMENDATIONS – keep the percentage of insiders typically top management to about 25 percent of less corporation’s membership. KEYWORDS–Corporate Governance, directors, officers, shareholders.
Keywords: INVESTIGATION; CORPORATIONS